Theoretical foundations for developing a regional system of medical services based on public–private partnership (PPP) production - Khamraeva Sayyora,; Otabekova Gulbadan Otabek kyzy, (THE INNOVATION ECONOMY, 2026)
The article provides a theoretical rationale for developing a regional system of medical services based on public–private partnership (PPP). Drawing on an analysis of domestic and international literature, the regulatory framework of the Republic of Uzbekistan, national statistics, and reports by analytical agencies, it identifies three core methodological frameworks: institutional, contractual, and systems approaches. It shows that the institutional environment determines the feasibility of PPP implementation; contract theory defines principles of risk allocation and payment mechanisms; and the systems approach requires integrating projects into a unified regional care network. The paper proposes ways to enhance effectiveness: ex-ante value-for-money (VfM) assessment, standard KPIs for replicable models, and stronger contract management within health authorities. The materials and conclusions are intended for the academic community and practitioners of regional health policy